Phone contact with parents contributed to emotional closeness and life satisfaction of Israeli and German students during 2010–2014 - Ifrah, Kfir; Bar-Tur, Liora; Lifshitz, Rinat; Lang, Frieder R. (Frontiers in Education, 2025)
IntroductionThis study explored the contribution of various contact modes of adult children with their parents to the children's emotional closeness with parents and to the children's life satisfaction.MethodsStudents at colleges and universities in Israel (N = 557) and in Germany (N = 535) were recruited during 2010-2011 and 2013-2014, respectively, through convenience sampling and completed web-based questionnaires reporting on the frequency of each contact mode with their parents (phone, in-person, and digital), their emotional closeness with their parents and their own satisfaction with life. Structural equation models tested the associations between the study variables among the Israeli and German samples while comparing them across the samples.ResultsThe results in both samples showed positive associations between the adult children's phone contact and emotional closeness with both parents and between in-person contact and emotional closeness with fathers. Among both samples, phone contact emerged as the strongest contributor to higher emotional closeness. Digital contact was associated with higher emotional closeness with both parents in the German sample only. Emotional closeness with either parent was associated with adult children's higher life satisfaction in both countries.DiscussionDuring the pre-COVID-19 era, in both Germany and Israel, direct and synchronous vocal communication contributed to intergenerational connections and wellbeing.